The relationship between the condition of the oral cavity and the use of tobacco products in different age groups - Moroka, R. K.; Povaliaiev, V. V.; Tkachenko, I. G.; Fomenko, Yu. V.; Babai, O. M.; Mikulinska-Rudich, Yu. N.; Iskorostenska, O. V.; Borisenko, Ye. Ye.; Nazaryan, R. S; Gargin, V. V. (Tbilisi : Nʹi︠u︡-Ĭork : Assot︠s︡iat︠s︡ii︠a︡ delovoĭ pressy Gruzii ; International Academy of Science, Education, Industry & Arts, 2024)
Understanding the harmful effects of using tobacco products (cigarettes, electronic cigarettes (e-cigarette) or vape, IQOS, hookah, etc.) by various segments of the population is one of the important ways to improve the condition of the tissues of the oral cavity, since smoking is an important risk factor for the occurrence of chronic destructive periodontal diseases. Aim: The purpose of our work was a study of the relationship between the state of the oral cavity and the use of tobacco products in different age groups based on the conducted questionnaire. Materials and methods: In order to conduct this research, an anonymous survey was conducted in the form of a Google document among people divided into three age groups: younger (under 21), middle (21-40) and older (over 40) with 1113 participants. In the survey, they answered questions about their lifestyle, the type of tobacco product used, visible changes of oral cavity if they were present. Results: Studies show that smoking and the use of tobacco products is a fairly common phenomenon in modern society and reflects a direct correlation between the intensity of this habit in people and the development of various pathological conditions of the mucous membranes of the mouth. A significant period of cigarette use, and the accompanying insufficiency of oral hygiene measures increase risk of oral cavity injury. More than 60% answered that they regularly brush their teeth twice a day. At the same time, at least half of all respondents answered that they use dental floss and mouthwashes irregularly, and also visit the dentist only when necessary. Among the first two age groups, it is noted that up to 52% of people consume various sweets and sweet drinks every day, which is a factor that contributes to the appearance of destructive changes in the oral cavity. Similar factors include the lack of an active lifestyle. So, from 30% to 50% in each age group don’t have any physical exercise. Only up to 30% of people have up to 3 physical exercises a week or have morning exercise every day. Conclusions: The most pronounced correlative relationship for severity of changes in oral cavity was revealed between with experience of smoking (how long) – r=0.79, intensity of smoking (r=0.75) and oral hygiene practices (r=0.71). It is necessary to develop new methods of combating the consequences of long-term use of tobacco products, as well as preventing the appearance of uncompensated changes in the mucous membrane of the oral cavity.
Financial support and sponsorship: No financial support was received for this study. Conflict of Interest Statement: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.
Keywords: MEDICINE; oral cavity; periodontal tissue; smoking; e-cigarette; survey